Revitalisasi Pendidikan Shalat Bagi Anak: Studi Takhrij dan Fiqh Al-Hadits - Laili, Syarifah; Dalimunthe, Nur Khoridah; Fatah, Nasrul (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2024)
Prayer is the main worship for a Muslim, throughout life cannot be replaced like other worship. In the hadith text, the Prophet's guidance is mentioned in an effort to educate children to pray. However, it gets a bad perception because it is considered permissive to acts of violence on children. So this study intends to elaborate on the validity of the hadith text in the Abu Daud narration and reveal its meaning and the scholars' understanding of it through the takhrij approach and fiqh al-hadith. This research is a literature research by taking a qualitative-analytical approach. It can be concluded that the hadith text in question meets the category of saheeh hadith because the sanad is connected to the Prophet and the narrators are considered positive. As for the meaning and meaning of the hadith, it is not a proof of the legality of harsh treatment of children, but is understood as a way to educate and discipline children in matters of prayer. The word